2022
DOI: 10.3390/brainsci12101358
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Coil Orientation on the Stimulation of the Pre–Supplementary Motor Area: A Combined TMS and EEG Study

Abstract: Studies using transcranial magnetic stimulation (TMS) have demonstrated the importance of direction and intensity of the applied current when the primary motor cortex (M1) is targeted. By varying these, it is possible to stimulate different subsets of neural elements, as demonstrated by modulation of motor evoked potentials (MEPs) and motor behaviour. The latter involves premotor areas as well, and among them, the presupplementary motor area (pre−SMA) has recently received significant attention in the study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
2
11
1
Order By: Relevance
“…The authors showed that brain oscillatory response modulations in the theta–alpha range are higher when E-field points anteriorly compared to any other tested orientation, while the same and other coil orientations showed higher brain oscillatory response modulations in the beta band. These results for spectral perturbation do not strictly match ours in terms of the coil orientations at which maximal effects are observed, possibly because in [ 29 ], the observed spectral perturbation is calculated for channels close to the stimulation site, thus capturing TMS-induced modulation of local induced activity, whereas our results capture long-range phase coupling of oscillatory brain activity.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…The authors showed that brain oscillatory response modulations in the theta–alpha range are higher when E-field points anteriorly compared to any other tested orientation, while the same and other coil orientations showed higher brain oscillatory response modulations in the beta band. These results for spectral perturbation do not strictly match ours in terms of the coil orientations at which maximal effects are observed, possibly because in [ 29 ], the observed spectral perturbation is calculated for channels close to the stimulation site, thus capturing TMS-induced modulation of local induced activity, whereas our results capture long-range phase coupling of oscillatory brain activity.…”
Section: Discussioncontrasting
confidence: 78%
“…Conversely, when the coil was oriented along the −115° macro-orientation, the maximal increase in functional connectivity between the left pre-SMA and the left motor cortex was observed. Several studies showed that the direction of the TMS coil influences brain responses, and there is already ample evidence of the importance of coil orientation for the stimulation of the primary motor cortex [ 25 , 29 , 30 , 50 , 51 , 52 ]. Less is known for the stimulation of SMA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we further verified the correspondence with a well-known brain atlas 54 to define the SMA-ROI for source analysis. Our localization was also verified comparing a recent study in which we specifically optimized the targeting and stimulation of the SMA using TMS–EEG 55 . Another limitation lies in the relatively low spatial resolution of our EEG recording, which did not allow to discriminate specific portions of the SMA.…”
Section: Discussionsupporting
confidence: 71%